Management of newly diagnosed transplant ineligible multiple myeloma. Issue 11 (18th September 2020) - Atrash, Shebli; Bhutani, Manisha; Paul, Barry; Voorhees, Peter M.; Usmani, Saad Z.
Abstract: Multiple myeloma (MM) is a chronically managed blood cancer with a median age of 69 years at the time of diagnosis. Although high dose melphalan and autologous stem cell transplantation (ASCT) remains a standard of care for eligible patients, more than half of the newly diagnosed MM patients are deemed ineligible due to comorbidities or complications of the disease by itself. In this setting, where ASCT is deemed inappropriate, patients could still achieve durable and deep responses if given the appropriate treatment plan. The key concepts of optimizing induction and maintenance strategies while minimizing side-effects are discussed in this review, especially in the context of employing novel agent combinations. It is important to understand the balance between safety and efficacy for each regimen, utilizing maintenance strategy and the best supportive care measures (bone health, infection prevention, and treatment, pain management, etc.). Here, we examine the evidence behind each of those principles and review results from clinical trials for transplant-ineligible (TI) MM.